A luminescence-based reporter to study tau secretion reveals overlapping mechanisms for the release of healthy and pathological tau - Lopez, Dianne Marquez; Maltby, Connor J.; Warming, Hannah; Divecha, Nullin; Vargas-Caballero, Mariana; Coldwell, Mark J.; Deinhardt, Katrin (Frontiers in Neuroscience, 2023)
In Alzheimer’s disease, tau pathology is thought to spread via a prion-like manner along connected neuronal networks. For this to occur, the usually cytosolic tau protein must be secreted via an unconventional mechanism prior to uptake into the connected neuron. While secretion of healthy and pathological tau has been documented, it remains under-investigated whether this occurs via overlapping or distinct processes. Here, we established a sensitive bioluminescence-based assay to assess mechanisms underlying the secretion of pseudohyperphosphorylated and wild-type tau in cultured murine hippocampal neurons. We found that under basal conditions, both wild-type and mutant tau are secreted, with mutant tau being more robustly secreted. Pharmacological stimulation of neuronal activity led to a modest increase of wild-type and mutant tau secretion, whereas inhibition of activity had no effect. Interestingly, inhibition of heparin sulfate proteoglycan (HSPG) biosynthesis drastically decreased secretion of both wild-type and mutant tau without affecting cell viability. This shows that native and pathological tau share release mechanisms; both activity-dependent and non-activity-dependent secretion of tau is facilitated by HSPGs.